(untitled) (ELang | An English Language Education Journal, 2022)
This study presents descriptive research at the second grade of SMK Tribakti Pangalengan. Research of English Education study program, Faculty of Teachers Training and Educational Sciences, Bale Bandung University, 2021. The research was conducted to analyze students’ error made by the second grade of SMK Tribakti Pangalengan of using auxiliary verbs in writing analytical exposition text. The research aimed to find the types of error in identifying auxiliary verbs based on surface taxonomy which consisted of omission, addition, misformation and misordering error. The method used is a qualitative descriptive method. The data of this research was collected through a writing test as the data instrument. The data sources of this study were the second grade of SMK Tribakti Pangalengan which consisted of 28 students. The researcher conducted the study by following the procedures of error analysis; identifying the errors, descripting the errors, explaining the errors and evaluating the errors. Furthermore, the data are collected through analyzing the sample of the students. The result of this research was that the student made errors in using auxiliary verbs in writing analytical exposition text. The result showed that students committed errors into four: omission, addition, misformation and misordering. There was an omission error which consisted of 62 errors or 28.83%. Next, there are 39 errors in addition or 18.13%. Misformation consisted of 100 errors or 46.51%. The last, there are 14 errors in misordering or 6.51%. In conclusion, the students still made errors in using auxiliary verbs in writing analytical exposition text. The highest frequency of error in students’ auxiliary verbs in writing analytical exposition text is misformation error.